Effects of Sterilization Techniques on Bioactivity of Polymethyl Methacrylate Antibiotic Beads Containing Vancomycin and Tobramycin. Issue 4 (April 2020) - Shaw, James; Gary, Joshua; Baker, Andrea; Kaplan, Heidi; Kim, Yesul; Milhoan, Madison; Burgess, Andrew; Ambrose, Catherine
Abstract : Objectives: Prefabrication and storage of antibiotic beads may decrease surgical time and allow for use in other settings. This study investigated the effects of sterilization technique and storage time on the bioactivity of antibiotic polymethyl methacrylate (PMMA) beads. Methods: Uniform beads of PMMA containing 1 g each of tobramycin and vancomycin were sterilized using autoclave, ethylene oxide (ETO), or ultraviolet (UV) light. Beads were made in a sterile fashion as a control. Disks containing eluted antibiotics from each of the 4 groups were placed onto agar plates inoculated with Staphylococcus aureus . Zones of inhibition, a measure of bioactivity for antibiotic eluted, were determined for the experimental groups and control. Repeat testing was performed for beads stored for 1 week, 1, 3, and 6 months. Results: Beads sterilized using autoclave, ETO, and UV light showed similar ZOIs after 24 hours of and 1 week of elution compared with the control group. Beads stored for up to 6 months demonstrated similar bioactivity to beads made sterile and tested immediately. Conclusion: PMMA beads containing vancomycin and tobramycin made in a sterile fashion and stored for up to 6 months have the same efficacy as the current standard of beads made sterile and used immediately. The elution and bioactivity of vancomycin–tobramycin antibiotic beads are not negatively impacted by the sterilization methods of autoclaving, ETO gas, or UV light. Furthermore, nonsterile beads can be sterilized and stored up to 6 months with an expected efficacy comparable with beads made in a standard sterile fashion.